On the First Stasimon of Sophocles' OT. - Barzakh, Zoia (Scripta Classica Israelica, 2025)
In my article, I analyze the first stasimon of Sophocles' OT (vv. 463-521) and its function in the dramatic context. I demonstrate that the Chorus of this stasimon is similar to both the spectator--in its collectivity and role of responsible citizens and judges, and to the hero--in its ignorance and preference for human skill over divinely inspired wisdom. In this way, through its mediation, the Chorus brings the hero's experience closer to that of the spectator and shows that his fatal ignorance is not a feature of his unique fate but an essential part of the human condition.